Thickness Characteristics of Pāhoehoe Lavas in the Deccan Province, Western Ghats, India, and in Continental Flood Basalt Provinces Elsewhere - Self, Stephen; Mittal, Tushar; Jay, Anne Elizabeth (Frontiers in Earth Science, 2021)
We provide the first global compilation of pāhoehoe lava-lobe thicknesses from various continental flood basalt provinces (~ 3800 measurements) to compare characteristic thicknesses within and between provinces. We refer to thin lobes (~ ≤ 5m), characteristic of “compound” lavas, as hummocky pāhoehoe lava flows or flow-fields. Conversely, we term thicker lobes, characteristic of “simple” flows, as coming from sheet-lobe-dominated flows. Data from the Deccan Traps and Columbia River flood-basalt provinces are archetypal since they have the most consistent datasets as well as established chemo- and litho-stratigraphies. Examining Deccan lobe thicknesses, we find that previously suggested (and disputed) distinct temporal and regional distributions of hummocky pāhoehoe and sheet-lobe-dominated flow fields are not strongly supported by the data and that each geochemically-defined formation displays both lobe types in varying amounts. Thin flow-lobes do not appear to indicate proximity to source. The modal lobe thickness of Deccan formations with abundant “thin” lava-lobes is 8m, while the mode for sheet-lobe-dominated formations is only 17m. Sheet-lobes up to 75-80m are rare in the Deccan and Columbia River Provinces, and ones > 100m are exceptional globally. For other flood basalt provinces, modal thickness plots show a prevalence towards similar lobe thicknesses to Deccan, with many provinces having some or most lobes in the 5-8m modal range. However, median values are generally thicker, in the 8-12m range, suggesting that sheet-lobes dominate. By contrast, lobes from non-flood basalt flow-fields (e.g., Hawai´i, Snake River Plain) show distinctly thinner modes, sub-5m. Our results provide a quantitative basis to ascertain variations in gross lava morphology and, perhaps, this will in future be related to emplacement dynamics of different flood basalt provinces, or parts thereof. We can also systematically distinguish outlier lobes (or regions) from typical lobes in a province; e.g., North American CAMP lava-lobes are anomalously thick and are closely related to feeder-intrusions, thus enabling a better understanding of conditions required to produce large-volume, thick, flood basalt lava-lobes and flows.